온라인 기반 인지 지능 검사(Cognitive Intelligence Test)의 유효성 평가 - 김준우(Joonwoo Kim); 김상엽(Sangyub Kim); 이솔빈(Solbin Lee); 구민모(Min-Mo Koo); 남기춘(Kichun Nam) (디지털콘텐츠학회논문지, 2022)
본 연구는 인지신경과학의 이론과 측정 기술, 인공지능 예측 시스템을 이용하여 인지기능 프로파일을 제공하는 온라인 기반 인지 지능 검사 프로그램 (CIT; Cognitive Intelligence Test)을 소개하고, 실제 상황에 적용 가능한지를 평가한 결과를 제시한다. 해당 프로그램은 작업기억, 주의, 운동 통제, 문제해결, 의사 결정의 능력을 온라인으로 측정하는 기술을 통하여 전반적인 기능에서 특화된 기능까지 사용자 맞춤형 뇌 기능 검사를 실시한다. 본 프로그램의 유효성을 검증하기 위하여, 연령별 운전자, 게이머 및 비게이머 집단을 대상으로 한 두 실험을 통하여 인지 능력을 측정 및 비교하였다. 연구 결과, 두 실험 모두에서 연령에 따른 인지 기능 저하를 보여주어 인지 노화를 적절하게 측정할 수 있었다. 이러한 결과는 해당 인지 지능 검사가 연구 현장과 응용 시스템에서 폭넓은 실제 사용자를 대상으로 유용하게 사용될 수 있음을 보여준다. The purpose of the current study was to introduce the online-based Cognitive Intelligence Test (CIT) developed on the basis of the theory and measurement of cognitive neuroscience, and to evaluate whether it is applicable to real-world situation. The online-based CIT provides personalized measurement on five main cognitive abilities: working memory, attention, motor control, problem solving, and decision making. Two experiments were carried out to measure and compare cognitive abilities of gamers versus non-gamers and drivers with various age groups, respectively. The results showed that the CIT could examine decline in cognitive abilities by age (i.e., cognitive aging) in both experiments. In conclusion, the current study suggests that the online-based CIT is useful for research field and for constructing the application system related with human cognition. KCI Citation Count: 1